2018
DOI: 10.3897/subtbiol.27.25777
|View full text |Cite
|
Sign up to set email alerts
|

Neocarus spelaion sp. n. (Parasitiformes, Opilioacaridae), a new species of cave dwelling Neocarus from Minas Gerais state, Brazil

Abstract: A new cave dwelling species of the genus Neocarus (Parasitiformes: Opilioacarida: Opilioacaridae) is described from adult females and males collected in Minas Gerais state, southeast Brazil. Five or six d-type setae on palps, females with pregenital area hairless, genital setae smooth, cylindrical ovipositor with two terminal lobes, and males with genital and pregenital setae variable in shape, some being smooth and pointed, others ribbed and pointed, are the combinations of characters that define the new spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…11). Small abnormalities in body setae (Araújo et al 2018a) or the duplication of pores (Bernardi and Borges-Filho 2018) has been observed in other species. Here, for the first time, abnormalities are seen in complete structures, such as the palp.…”
Section: Development and Morphological Abnormalitiesmentioning
confidence: 64%
See 4 more Smart Citations
“…11). Small abnormalities in body setae (Araújo et al 2018a) or the duplication of pores (Bernardi and Borges-Filho 2018) has been observed in other species. Here, for the first time, abnormalities are seen in complete structures, such as the palp.…”
Section: Development and Morphological Abnormalitiesmentioning
confidence: 64%
“…The number of described species of Opilioacarida from collections in karst areas and caves in Brazil is increasing (Bernardi et al 2013b(Bernardi et al , c, 2014Araújo et al 2018a;Bernardi and Borges-Filho 2018). This is due to the intensification of sampling efforts in this habitat as the result of environmental licensing processes.…”
Section: Final Remarksmentioning
confidence: 99%
See 3 more Smart Citations